More stories from grandma's attic - Richardson, Arleta (Elgin, IL : Chariot Books, 1979)
A collection of stories of life in the late nineteenth century, many reflecting the Christian faith of the author's family, including tales of a contest for the best handiwork, a pig asleep in a baby carriage, and a visitor without a name.
Sequel to: In grandma's attic.
Sequel: Still more stories from Grandma's attic.
Keywords: Country life -- Michigan -- Fiction; Christian life -- Fiction; Michigan -- Fiction; United States -- Social life and customs -- 1865-1918 -- Fiction